Hydrothermal synthesis of zeolites-calcium silicate hydrate composite from coal fly ash with co-activation of Ca(OH)2-NaOH for aqueous heavy metals removal - Li, Guanghui; Li, Min; Zhang, Xin; Cao, Pengxu; Jiang, Hao; Luo, Jun; Jiang, Tao (International journal of mining science and technology, 2022)
Coal fly ash is a typical secondary aluminum/silicon resource. The preparation of zeolite-type absorbent is a potential way for its value-added utilization, while the purity and adsorption property of zeolite are limited due to the occurrence of side reactions in the synthesis process. In this study, a designated composite consisted of crystalline zeolites and amorphous calcium silicate hydrate was selected, which was direct synthesized from fly ash under conditions of a Ca/Si molar ratio of 0.8, an initial NaOH concentration of 0.5 mol/L, a hydrothermal temperature of 170 ℃ and a liquid–solid ratio of 15 mL/g. The results indicated that this composite had superior adsorption property for a variety of heavy metals, which was based on the exchange of calcium and sodium ions in zeolites and calcium silicate hydrate. Its adsorption capacities for Pb2+, Ni2+, Cd2+, Zn2+, Cu2+ and Cr3+ attained 409.4, 222.4, 147.5, 93.2, 101.1 and 157.0 mg/g, respectively, in single solution with a pH of 4.5. After regulating the synthesis conditions, the transformation of amorphous calcium silicate hydrate into crystallized tobermorite weakened the adsorption capacity of the composite. Besides, due to the competitive adsorption in a multiple ions solution, the adsorption capacities for these heavy metals had a reduction.